2021
DOI: 10.2147/jmdh.s293378
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prognosis in Patients with COVID-19 and Liver Injury: A Retrospective Analysis

Abstract: Purpose COVID-19 is a new infectious disease with global spread. The aim of the present study was to explore possible risk factors and evaluate prognosis in COVID-19 with liver injury. Methods A retrospective study was conducted on 356 COVID-19 patients in the Third People’s Hospital of Yichang, Hubei, China. Clinical characteristics and laboratory tests between patients with and without liver injury were compared, while risk factors of COVID-19–related liver injury wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…In agreement with our findings, Pazoki et al showed that high serum levels of ALP and AST was a risk factor of in-hospital mortality and disease severity in diabetic patients with confirmed or clinically suspected COVID-19 [ 27 ]. Shen et al reported a similar findings [ 32 ]. However, liver damage and increased levels of liver enzymes in serum including AST and ALP is also reported in the diabetic patients in Islam et al study [ 33 ].…”
Section: Discussionsupporting
confidence: 67%
“…In agreement with our findings, Pazoki et al showed that high serum levels of ALP and AST was a risk factor of in-hospital mortality and disease severity in diabetic patients with confirmed or clinically suspected COVID-19 [ 27 ]. Shen et al reported a similar findings [ 32 ]. However, liver damage and increased levels of liver enzymes in serum including AST and ALP is also reported in the diabetic patients in Islam et al study [ 33 ].…”
Section: Discussionsupporting
confidence: 67%
“…All published literature which analyzed liver biochemical parameters in COVID-19 patients was examined through databases and shown in Table 1 [ 5 , 6 , 11 , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. Based on previous studies, liver biochemical parameters abnormalities were defined as the elevation of the following liver enzymes in serum: ALT > 40 U / L, AST > 40 U / L, and total bilirubin> 1.20 mg/d l. As in a previous study, we defined ALT and/or AST over three times upper limits of normal (ULN), and/or total bilirubin over two times ULN as liver injury [7] .…”
Section: Methodsmentioning
confidence: 99%
“…Apparently, male sex, older age, and higher body mass index are also associated with liver damage from COVID-19[ 6 , 17 , 58 , 59 ]. Besides, coexisting diseases such as hypertension, diabetes, cardiovascular disease, malignancy, and some liver diseases may all be risk factors for liver damage[ 60 , 61 ]. Currently, the susceptibility of children and pregnant women to liver injury is not fully understood.…”
Section: Risk Factors For Liver Injurymentioning
confidence: 99%